Acute Hemodynamic Effect of Acetazolamide in Patients With Pulmonary Hypertension Whilst Breathing Normoxic and Hypoxic Gas: A Randomized Cross-Over Trial - Lichtblau, Mona; Berlier, Charlotte; Saxer, Stéphanie; Carta, Arcangelo F.; Mayer, Laura; Groth, Alexandra; Bader, Patrick R.; Schneider, Simon R.; Furian, Michael; Schwarz, Esther I.; Swenson, Erik R.; Bloch, Konrad E.; et al. (Frontiers in Medicine, 2021)
Aims: To test the acute hemodynamic effect of acetazolamide in patients with pulmonary hypertension (PH) under ambient air and hypoxia. Methods: Patients with pulmonary arterial or chronic thromboembolic PH (PAH/CTEPH) undergoing right heart catheterization were included in this randomized, placebo-controlled, double-blinded, crossover trial. The main outcome, pulmonary vascular resistance (PVR), further haemodynamics, blood- and cerebral oxygenation were measured 1h after intravenous administration of 500mg acetazolamide or placebo-saline on ambient air and at the end of breathing hypoxic air (FIO2 0.15) for 15min. Results: 24 PH-patients, 71% men, mean±SD age 59±14 years, BMI 28±5 kg/m2, PVR 4.7±2.1 WU participated. Mean PVR after acetazolamide vs. placebo was 5.5±3.0 vs. 5.3±3.0 WU; mean difference (95% CI) 0.2 (-0.2 to 0.6, p=0.341). Heart rate was higher after acetazolamide (79±12 vs. 77±11 bpm, p=0.026), pH was lower (7.40±0.02 vs. 7.42±0.03, p=0.002) but PaCO2 and PaO2 remained unchanged while cerebral tissue oxygenation increased (71±6 vs 69±6%, p=0.017). In acute hypoxia, acetazolamide decreased PVR by 0.4 (0.0 to 0.9, p=0.046) while PaO2 and PaCO2 were not changed. No adverse effects occurred. Conclusions: In patients with PAH/CTEPH, i.v. acetazolamide did not change pulmonary haemodynamics compared to placebo after one hour in normoxia but it reduced PVR after subsequent acute exposure to hypoxia. Our findings in normoxia do not suggest a direct acute pulmonary vasodilator effect of acetazolamide. The reduction of PVR in hypoxia requires further corroboration. Whether acetazolamide improves PH when given over a prolonged period by stimulating ventilation and increasing oxygenation remains to be investigated.